Dew benefits on alpine grasslands are cancelled out by combined heatwave and drought stress - Li, Yafei; Eugster, Werner; Riedl, Andreas; Lehmann, Marco M.; Aemisegger, Franziska; Buchmann, Nina (Frontiers in Plant Science, 2023)
Increasing frequencies of heatwaves combined with simultaneous drought stress in Europe threaten the ecosystem water and carbon budgets of alpine grasslands. Dew as an additional water source can promote ecosystem carbon assimilation. It is known that grassland ecosystems keep high evapotranspiration as long as soil water is available. However, it is rarely being inves-tigated whether dew can mitigate the impact of such extreme climatic events on grassland eco-system carbon and water exchange. Here we use stable isotopes in meteoric waters and leaf sugars, eddy covariance fluxes for H2O vapor and CO2, in combination with meteorological and plant physiological measurements, to investigate the combined effect of dew and heat-drought stress on plant water status and net ecosystem production (NEP) in an alpine grassland (2000 m elevation) during the June 2019 European heatwave. Before the heatwave, enhanced NEP in the early morning hours can be attributed to leaf wetting by dew. However, dew benefits on NEP was cancelled out during the heatwave, due to the minor contribution of dew in leaf water. Heat-induced reduction in NEP was intensified by the combined effect of drought stress. The recov-ery of NEP after the peak of the heatwave could be linked to the refilling of plant tissues during nighttime. Among-genera differences of plant water status affected by dew and heat-drought stress can be attributed to differences in their foliar dew water uptake, and their reliance on soil moisture or the impact of the atmospheric evaporative demand. Our results indicate that dew influence on alpine grassland ecosystems varies according to the environmental stress and plant physiology.